2022
DOI: 10.14814/phy2.15460
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of gonadotropin secretion along the estrous cycle of C57BL/6 female mice

Abstract: The pattern of gonadotropin secretion along the estrous cycle was elegantly described in rats. Less information exists about the pattern of gonadotropin secretion in gonad‐intact mice, particularly regarding the follicle‐stimulating hormone (FSH). Using serial blood collections from the tail‐tip of gonad‐intact C57BL/6 mice on the first day of cornification (transition from diestrus to estrus; hereafter called proestrus), we observed that the luteinizing hormone (LH) and FSH surge cannot be consistently detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Secondly, the Kiss1 AVPV neurons infected with EYFP virus occupy only a small proportion (<5%). It is unlikely that this number of Kiss1 AVPV neurons with ChR2-EYFP could evoke an LH surge, because it was previously shown that mice failed to exhibit an LH surge when 14% of Kiss1 AVPV neurons were activated ( 48 ). At the same time, the LH dynamics are also different with Kiss1 AVPV cell bodies stimulation ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the Kiss1 AVPV neurons infected with EYFP virus occupy only a small proportion (<5%). It is unlikely that this number of Kiss1 AVPV neurons with ChR2-EYFP could evoke an LH surge, because it was previously shown that mice failed to exhibit an LH surge when 14% of Kiss1 AVPV neurons were activated ( 48 ). At the same time, the LH dynamics are also different with Kiss1 AVPV cell bodies stimulation ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, P-2 and P-1 are metestrus or diestrus, and P+1 is estrus. P+2 is estrous and metestrus (see also 34 ). We did not identify signi cant differences between estrous stages or between intact and ovariectomized females (Figure 3E, see also Figure S3).…”
Section: Vip Acts Directly On Gnrh Neurons Through Vpac2 To Regulate ...mentioning
confidence: 99%
“…It is characterized by an increase in E2 followed by the GnRH/LH surge usually occurring at the light/dark transition (Gusmao et al., 2022; Miller & Takahashi, 2014; Walmer et al., 1992). Estrus: The LH surge triggers the release of oocytes from the ovary (ovulation); this estrous stage is the period of sexual receptivity lasting ∼1 day, by the end of which E2 and LH levels return to basal (Goldman et al., 2007; Gusmao et al., 2022; Walmer et al., 1992). Metestrus and diestrus: Metestrus is followed by the diestrus stage, both of which are characterized by low basal levels of E2 and LH, together generally lasting 2 to 3 days (Goldman et al., 2007; Gusmao et al., 2022; Walmer et al., 1992).…”
Section: Introductionmentioning
confidence: 99%
“… Proestrus: This is the pre‐ovulatory stage, which lasts <12 to 24 hr. It is characterized by an increase in E2 followed by the GnRH/LH surge usually occurring at the light/dark transition (Gusmao et al., 2022; Miller & Takahashi, 2014; Walmer et al., 1992). Estrus: The LH surge triggers the release of oocytes from the ovary (ovulation); this estrous stage is the period of sexual receptivity lasting ∼1 day, by the end of which E2 and LH levels return to basal (Goldman et al., 2007; Gusmao et al., 2022; Walmer et al., 1992).…”
Section: Introductionmentioning
confidence: 99%